METAMORFOSE: A RELEVÂNCIA DO TEMA EM NARRATIVAS ORAIS DA AMAZÔNIA PARAENSE - Simões, Maria do Socorro (Organon, 2007)
The text here presented it is a type of demonstration of the privilege granted to the theme of the metamorphosis in popular oral narratives of the paraense Amazonia.